EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND PROFITABILITY ON STOCK PRICES - Rosa Zulfikhar; Wildoms Sahusilawane; Dian Rokhmawati; Supiati Supiati; Mawardi Mawardi (Bajang Institute, 2023)
The purpose of this research is to analyze effect of corporate social responsibility and profitability on stock prices. This research is a type of explanatory research. The population in this study is the Food and Beverage Industry on the Indonesia Stock Exchange during the period 2019 to 2022, namely 51 companies. The sample of this study are companies that actively issued corporate social responsibility during the research period, namely the Food and Beverage Industry on the Indonesia Stock Exchange, totaling 11 companies. Hypothesis testing uses partial (t) test. The results of the study show that corporate social responsibility has a significant effect on stock prices. Profitability has a significant effect on stock prices.